Magyarország mint befektetési célország-japán szemmel - Kawakita, Shinken (Marketing & Menedzsment, 2019)
In October 1994 I visited Budapest, because JOI was commissioned last spring by Japan's Ministry of Finance (MOF) to conduct research on the investment climate in Central Europe (i.e. the four countries of Poland, Czech Rep., Slovak Rep., and Hungary). Our research focused on the up-to-date political & economic status, FDI systems, business activities of U.S., European and Japanese companies and others. We conducted the field survey last October and submitted our report to MOF this February. This article is based upon the information which we obtained through our field survey in Hungary and hearings at companies in Japan concerned with Hungary. I will begin with a brief outline of the trend of Japanese overseas investment, and then turn to the main topic of today, that is, the Japanese view of Hungary as an investment destination. I will specifically and objectively introduce to you the actual & frank answers to our questions obtained at the hearings with Japanese companies, item by item, including the motives for their Hungarian investments, and the business performance in Hungary. In conclusion, I will discuss the recommendations for promotion of Japanese investment in Hungary, which will be titled "A view of the future (one approach)".